Observation of changes in the eye and joints due to the modification of therapy for ankylosing spondylitis and recurrent uveitis – a twenty-year follow-up study - Płatkowska-Adamska, Bernadetta; Kal, Magdalena; Pater, Ewa; Maciejowska-Roge, Maria; Biskup, Jan; Biskup, Michał; Odrobina, Dominik (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
We present a twenty-year follow-up study of a patient and changes in his eyes and joints under various therapies for ankylosing spondylitis. Sulfasalazine, methotrexate, etanercept and adalimumab were used to treat the systemic disease. Ophthalmological treatment of recurrent uveitis occurring every 2 months included intravenous dexamethasone, oral prednisone and topical dexamethasone and 1% tropicamide. Long-term treatment with steroids resulted in complications such as cataracts and herpetic keratitis. Prior to treatment with adalimumab, treatment-resistant, recurrent uveitis and complications such as proliferative vitreoretinopathy and secondary retinal detachment resulted in irreversible lesions and blindness in the right eye. By switching the TNF-α inhibitor to adalimumab for rheumatological ailments, the patient achieved significant improvement in visual acuity in the left eye and a long-term absence of inflammatory symptoms in this eye, which confirms that in the case of spondyloarthropathy, the cooperation of a rheumatologist and an ophthalmologist is necessary.